SISTEM PENGGEMBALAAN SEBAGAI ALTERNATIF PETERNAKAN SAPI POTONG YANG EFEKTIF DAN EFISIEN - Yoselanda Marta (Udayana University, 2015)
Raising of livestock, especially cattle is still faced with problems of a continuous supply of green feed. Nearly 70% of production costs and maintenance expenditure sourced from cattle feed. Labor efficiency being one of the problems that have not been resolved. Various methods were developed to find a solution that will be able to resolve problems that arise. Breakthroughs were made to bring the solution to be developed. One is to do with the method of pasture grazing system. With this system is expected able to resolve the issues. This method is considered appropriate to be applied as to minimize feed costs and streamline workforce.Keywords : feed, workforce, cost value